Pembelajaran Jarak Jauh dan Dampaknya terhadap Hasil Belajar Siswa Sekolah Dasar - Gita Aura; Ibnu Muthi (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
This study aims to analyze the impact of Distance Learning (PJJ) on the learning outcomes of elementary school students during the COVID-19 pandemic. In its implementation, PJJ presents various challenges, including decreased learning outcomes (learning loss), lack of student involvement, low concentration, and limited learning facilities. Inhibiting factors such as access to technology, minimal parental guidance, and lack of motivation for independent learning also worsen the condition. However, various strategies have been implemented by teachers and parents to overcome these obstacles, ranging from variations in learning methods, strengthening communication, to creating a conducive learning environment. The results of the analysis show that collaboration between teachers and parents is very important in maintaining the quality of learning. This study also found a significant difference between learning outcomes before and during PJJ, where face-to-face learning tends to provide better results. This study recommends the need to strengthen educational infrastructure and increase the digital capacity of all elements of education as an effort to face similar challenges in the future.